Can IgG Antibodies Directed against Different Targets Solve the Problem of False-Positive Results in SARS-CoV-2 Serology? - Nataša Beader; Ivana Ivana Mareković (Acta Clinica Croatica, 2021)
In addition to RT-PCR assays, serology testing that has been recognized as a useful tool to assess the spread of infection in the population is considered successful and important strategy in the control of the global pandemic of SARS-CoV-2 infection. Now, a great number of manufacturers offer their serologic tests on the market. When interpretating the results, the rate of seroprevalence should be taken in consideration because it may influence the positive predictive value, as well as cross-reactivity with other coronaviruses in case of assays with poorly designed antigens. We present results of 11 patients with different clinical background and tested with two different serologic tests, DIAPRO (ELISA; Sesto San Giovanni, Italy) and VIDAS (ELFA; BioMerieux, Marcy I’Etoile, France). The results obtained by the former test showed ten of these patients to be IgG positive and one patient was IgG weakly positive with different confidence index. The latter test discriminated positive results with medium confidence index on the former test as negative. The results obtained with two serology tests were concordant with the observation that the results with medium confidence index may indicate cross-reactivity.